The Effects of Financial Literacy on the Profitability of SMEs in Malang District, Indonesia - Susilowati, Kartika Dewi Sri; Riwajanti, Nur Indah; Ekasari, Kurnia (Applied Business and Administration Journal, 2025)
This study investigated the relationship between financial literacy—which encompasses financial behavior, attitudes, and knowledge—and the profitability of small and medium enterprises in the food and beverage industry in Malang District, Indonesia. The data were collected using a questionnaire distributed to 107 business owners and managers. The relationship between profitability and financial literacy, including financial behavior, attitudes, and knowledge, was examined using multiple linear regression analysis. The results of the analysis showed a significant positive influence of financial attitude and knowledge on profitability. Financial behavior, however, had no impact on profitability. The results of this study are expected to increase the awareness of the government and related financial organizations regarding the significance of financial literacy for SMEs, particularly in relation to programs designed to improve their business capacity through financial literacy training and education.